The church has AIDS: towards a positive theology for an HIV+ church - Forster, Dion (Epworth Review, 2010)
One of the most controversial statements in the contemporary Church is surely the assertion that ‘The Church has AIDS’! This statement challenges Christians to recognize that it is impossible to do theology and engage in Christian life and ministry without taking into account the impact of HIV and AIDS on the world. Susan Rakoczy reminds us that theologians, and all Christians who take their belief in Christ seriously, have a responsibility to forge a positive theology of HIV/AIDS, since sadly so much of the Church’s official and popular rhetoric has sent the false message that at best God is silent on HIV and AIDS, and at worst God is either punishing persons with AIDS or has abandoned us in our suffering.
Free
Keywords: AIDS (Disease); Christians – South Africa; Church – History of doctrines – 2000; Church work with the sick; Community – Religious aspects – Christianity; Epidemics; HIV (Viruses); Relation (Theology); Suffering